Efektivitas Program Penambahan Jam Pelajaran Matematika pada Siswa Kelas XII Madrasah Aliyah - Sapti Wahyuni (JURNAL RISET RUMPUN MATEMATIKA DAN ILMU PENGETAHUAN ALAM, 2022)
One of the most important problems to be addressed is the low achievement of students in mathematics. This needs to be addressed immediately considering that mathematics is the science most often used in the world of work. The purpose of this study was to determine the effectiveness of additional hours of mathematics lessons on improving mathematics learning achievement of class XII MIPA students. This research is categorized as evaluation research using the CIPP model (context, input, process, and product). The population studied was all students of class XII MIPA MAN 3 Bantul in the 2016/2017 academic year, totaling 64 people. The condition before the learning process was carried out with the addition of study hours obtained an average value of 34.10 while after the addition of hours the acquisition increased to 44.16 or an increase of 29.50%. The results of the t-test analysis showed that there were significant differences in the results of learning mathematics before additional hours were added.